A patient with chest pain and a high‐risk ECG pattern: The Wellens' syndrome. Issue 4 (29th March 2023) - Baasen, Sven; Stern, Manuel; Veulemans, Verena; Bönner, Florian; Kelm, Malte; Busch, Lucas
Abstract: This case highlights the ECG interpretation in acute coronary syndrome absence from ST – elevation myocardial infarction. A patient with acute chest pain and biphasic T – waves or deep inverted T‐ waves in V2–V3 is at risk for myocardial infarction. Timely cardiological assessment and coronary angiography is required. Abstract : This case highlights the ECG interpretation in acute coronary syndrome absence from ST – elevation myocardial infarction. A patient with acute chest pain and biphasic T – waves or deep inverted T‐ waves in V2–V3 is at risk for myocardial infarction. Timely cardiological assessment and coronary angiography is required.